Physics for scientists & engineers with modern physics - GORDON JOHN R. 2004 (USA Thomson learning, 2004)
"I was motivated from the beginning to write a textbook different from others that present physics as a sequence of facts, like a Sears catalog: "here are the facts and you better learn them." Instead of that approach in which topics are begun formally and dogmatically, I have sought to begin each topic with concrete observations and experiences students can relate to: start with specifics and only then go to the great generalizations and the more formal aspects of a topic, showing why we believe what we believe. This approach reflects how science is actually practiced"--
Introduction, measurement, estimating -- Describing motion: kinematics in one dimension -- Kinematics in two or three dimensions; vectors -- Dynamics: Newton's laws of motion -- Using Newton's laws; friction, circular motion, drag forces -- Gravitation and Newton's synthesis -- Work and energy -- Conservation of energy -- Linear momentum -- Rotational motion -- Angular momentum; general rotation -- Static equilibrium; elasticity and fracture -- Fluids -- Oscillations -- Wave motion -- Sound -- Temperature, thermal expansion, and the ideal gas law -- Kinetic theory of gases -- Heat and the first law of thermodynamics -- Second law of thermodynamics -- Electric charge and electric field -- Gauss's law -- Electric potential -- Capacitance, dielectrics, electric energy storage -- Electric currents and resistance -- DC circuits -- Magnetism -- Sources of magnetic field -- Electromagnetic induction and Faraday's law -- Inductance, electromagnetic oscillations, and AC circuits -- Maxwell's equations and electromagnetic waves -- Light; reflection and refraction -- Lenses and optical instruments -- The wave nature of light; interference and polarization -- Diffraction -- The special theory of relativity -- Early quantum theory and models of the atom -- Quantum mechanics -- Quantum mechanics of atoms -- Molecules and solids -- Nuclear physics and radioactivity -- Nuclear energy; effects and uses of radiation -- Elementary particles -- Astrophysics and cosmology.
Includes bibliographical references and index.
Keywords: Physics -- Textbooks